Prevalence and genetic etiology of poly-cystic ovarian syndrome (PCOS) in Mauritania - Elwafi, Marieme; Ahmed, Abdi; Akhouayri, Omar; Zein, Ahmed; Abdelkader, Hamma; Selman, Roughaya; Houmeida, Ahmed (Frontiers in Reproductive Health, 2025)
BackgroundPolycystic ovary syndrome (PCOS) is a common endocrine and metabolic disorder characterized by polycystic ovaries, oligoanovulation, hyperandrogenism and infertility. The exact specific causes of this disease have not yet been identified, but there is evidence of significant genetic involvement.ObjectiveThe present study aimed to evaluate the prevalence of PCOS and explore its gene polymorphisms in the Mauritanian population.Material and methodsFiles of 2,100 women patients attending two gynaecologic clinics of Nouakchott were retrospectively analysed to identify PCOS patients based on the 2003 Rotterdam Criterion. A genetic study used Sanger sequencing to search for six known SNPs in LHCGR (rs2293275), FSHR (rs6166), ESR1 (rs2234693), GnRHR (rs104893836), miR-126 (rs4636297), and miR-499 (rs3746444) among 8 familial PCOS cases and 3 sporadic patients. A more extended search was then carried out exclusively for LHCGR rs2293275 on 56 PCOS patients.ResultsThe prevalence of PCOS was 7.8% in this cohort. The occurrence of LHCGR rs2293275 (T>C, G; p. Asn 312 Ser) and ESR1 rs2234693 (T>C, G) polymorphisms in the PCOS screened patients suggests a likely association of these variants with the disease. However, rs104893836 polymorphism was not found in any of the tested PCOS cases.ConclusionAlthough yet to be confirmed in larger size cohort, these data could contribute to improving the exploration, referral, and treatment of PCOS in Mauritania.